Gastric Calcifying Fibrous Tumour - Tan Attila; Dean Chen; Geoffrey W Gardiner; Theadore W Ptak; Norman E Marcon (Canadian Journal of Gastroenterology)
Intramucosal gastric tumours are most commonly found to be gastrointestinal stromal tumours or leiomyomas (smooth muscle tumours); however, a variety of other uncommon mesenchymal tumours can occur in the stomach wall. A rare benign calcifying fibrous tumour is reported and the endoscopic appearance, ultrasound findings and morphology are documented. A review of the literature found only two similar cases.